Political Dynamics of the Era of Ali Bin Abi Thalib (Contribution of the Political System in Islamic Civilization) - Aldzakhiroh, Nilna; Nopriansyah, Beri; Ramadhani, Gita Fitri; Mubaraq, Zulfi; Kholid, Nur (Universitas Islam Negeri Sumatera Utara, 2024)
The study of political studies during the time of Caliph Ali bin Abi Thalib is very important to study in more depth. Because this study greatly contributes to political problems in Indonesia such as corruption and social injustice which are often debated. The aim of this article is to understand 3 things: First, the political paradigm of Ali bin Abi Talib's time. Second, internal and external factors that influenced the politics of Ali bin Abi Talib's time. Third, the positive and negative implications of politics for Muslims at that time. The method used is qualitative research with a literature review approach. The results found were 3 things: First, the political paradigm of Ali bin Abi Talib's time had 3 forms: (1) war politics (2) peace (3) justice. Second, internally there were 3 factors that influenced it: (1) differences of opinion (2) Caliph Ali's policies (3) Caliph Ali's characteristics. Externally, there are 5 factors that influence it: (1) the death of Muslims (2) support from the Kuffah community (3) the Governor's negligence (4) community problems (5) selfishness. Third, there are 3 positive implications for Muslims: (1) making it easier for Caliph Ali (2) the emergence of different forms of Islamic law (3) an orderly government system. Meanwhile, the negative implications for Muslims are 3 things: (1) changes in the Islamic government system (2) the emergence of new groups (3) division of Muslims. The conclusion of this article shows that it provides new views and insights into the study of Islamic Civilization during the era of Caliph Ali bin Abi Talib in the current political sector.